2020
DOI: 10.1111/jpm.12627
|View full text |Cite
|
Sign up to set email alerts
|

Mental health stigma among Middle Eastern adolescents: A protocol for a systematic review

Abstract: Accessible Summary What is known on the subject? Four out of every five people with mental health disorders face stigma. Mental health and, consequently, mental health stigma are very common among youth living in the Middle East countries. Several studies have investigated mental health among adolescents in the Middle East, but studies on stigma are very scattered. There is no systematic review on stigma among adolescents with mental disorders across all the Middle East countries despite the common historica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…Demographic and socio-demographic sensitivity such as gender and ethnicity/culture will be carefully considered in the sampling process. Adolescents in the early stage (aged 12-14 years) will not be included in the data collection as their daily plans are mostly influenced by their families, especially in the Middle East culture (18,31).…”
Section: Participants and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic and socio-demographic sensitivity such as gender and ethnicity/culture will be carefully considered in the sampling process. Adolescents in the early stage (aged 12-14 years) will not be included in the data collection as their daily plans are mostly influenced by their families, especially in the Middle East culture (18,31).…”
Section: Participants and Samplingmentioning
confidence: 99%
“…Overall, it has been approximated that more than 90% of asylum seeking children and adolescents that need mental health services, never receive them (15). Thus, the time for decreasing adolescents' psychological problems is limited and any delay in effective actions significantly increases the time span of recovery and severity of the problems (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…This issue applies both to developed and developing countries, although there are variations in how relevant data are collected. The World Health Organization reported in 2020 that 10–20% of children and adolescents worldwide experience mental disorders [ 2 ]. The World Bank reported in 2006 that for young people, neuropsychiatric disorders are a leading cause of health-related burden, accounting for 15–30% of the disability-adjusted life-years (DALYs) lost during the first three decades of life [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is a complicated critical life stage that bridges childhood to adulthood [ 2 ]. Psychological problems of children and adolescents not only affect their academic performance and social interactions, but also contribute to serious problems in adulthood, including unemployment, drug use, and crime [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study found that mental disorders were 1.54 times more likely to be stigmatized than other conditions [11]. Another study revealed that four in five people with a mental disorder are stigmatized by their environment [12]. The stigma of mental disorders is the result of four components processes: cognitive (labeling and stereotyping), emotional (prejudice), behavioral (discrimination), and structural (the accumulated organizational policies and practices) causing injustice to people with a mental disorder.…”
Section: Introductionmentioning
confidence: 99%